PENGEMBANGAN DATA LOGGER SUHU AIR BERBIAYA RENDAH - Muhammad Idris; Indra Jaya (Fakultas Perikanan dan Ilmu Kelautan, 2014)
Water temperature data logger is an instrument to record thewater temperature automatically andcapable ofmonitoring of temperature condition of the medium or environment. This research aims to design and construct low cost water temperature data logger. Casing of the logger was designed using cylindric aluminum material with a diameter of 3.20 cm and a length of 16.50 cm. The electronic systemswere built from the microcontroller ATmega 328P as main controller, DS18B20 as temperature sensor, mini DC motor as vibration indicator, DS3231 as time marker sensor, and micro SD card as data storage. The result offield test showed that casing was waterproof and did not need an addition of ballast. The battery life time is 10 days 8 hours for 30 minutes sampling intervals The range error value of sensor calibration is between (-0.37)-0.41°C and RMSE value 0.23 °C. The result of measurement in Bogor Agricultural University lake on October 10th –20th 2013 ranged from 27.69-31.63 °C with the lowest daily temperature at 5.30-8.30 WIB and the highest at 12:00 -16:00 WIB. T test comparison of data between the water temperature data logger and a thermometer in thepond for two days showed that the data were not significantly different.